The broad-band SEDs of four 'hypervariable' AGN. Issue 3 (24th November 2017) - Collinson, James S; Ward, Martin J; Lawrence, Andy; Bruce, Alastair; MacLeod, Chelsea L; Elvis, Martin; Gezari, Suvi; Marshall, Philip J; Done, Chris
Abstract: We present an optical-to-X-ray spectral analysis of four 'hypervariable' AGN (HVAs) discovered by comparing Pan-STARRS data to that from the Sloan Digital Sky Survey over a 10 yr baseline (Lawrence et al.). There is some evidence that these objects are X-ray loud for their corresponding UV luminosities, but given that we measured them in a historic high state, it is not clear whether to take the high state or low state as typical of the properties of these HVAs. We estimate black hole masses based on Mg ii and H α emission line profiles, and either the high- or low-state luminosities, finding mass ranges log ( M BH /M⊙ ) = 8.2–8.8 and log ( M BH /M⊙ ) = 7.9–8.3, respectively. We then fit energy-conserving models to the spectral energy distributions (SEDs), obtaining strong constraints on the bolometric luminosity and αOX . We compare the SED properties with a larger, X-ray selected AGN sample for both of these scenarios, and observe distinct groupings in spectral shape versus luminosity parameter space. In general, the SED properties are closer to normal if we assume that the low state is representative. This supports the idea that the large slow outbursts may be due to extrinsic effects (for example microlensing) as opposed to accretion rate changes, but a larger sample of HVAs is needed to be confident of this conclusion.